Molecular targeted therapy of BRAF-mutant colorectal cancer. (June 2019) - Ducreux, Michel; Chamseddine, Ali; Laurent-Puig, Pierre; Smolenschi, Cristina; Hollebecque, Antoine; Dartigues, Peggy; Samallin, Emmanuelle; Boige, Valérie; Malka, David; Gelli, Maximiliano
Over the past two decades, the molecular characterization of metastatic colorectal cancer (mCRC) has been revolutionized by the routine implementation of RAS and BRAF tests. As a result, it is now known that patients with mCRC harboring BRAF mutations experience a poor prognosis. Although it accounts for only 10% of mCRC, this group is heterogeneous; only the BRAF- V600E mutation, also observed in melanoma, is associated with a very poor prognosis. In terms of treatment, these patients do not benefit from therapeutics targeting the epidermal growth factor receptor (EGFR). In first-line chemotherapy, there are two main options; the first one is to use a triple chemotherapy combination of 5-fluorouracil, irinotecan, and oxaliplatin, with the addition of bevacizumab, because post hoc analysis of randomized trials have reported interesting results. The other option is to use double chemotherapy plus bevacizumab, since anti-EGFR seems to have modest activity in these patients. Only a small percentage of patients who experience failure of this first-line treatment receive second-line treatment. Monotherapy with BRAF inhibitors has failed in this setting, and different combinations have also been tested. Using the rationale that BRAF inhibitor monotherapy fails due to feedback activation of the EGFR pathway, BRAF inhibitors have been combined with anti-EGFR agents plus or minus MEK inhibitors; however, the results did not live up to the hopes raised by the concept. To date, the best results in second-line treatment have been obtained with a combination of vemurafenib, cetuximab, and irinotecan. Despite these advances, further improvements are needed.